PEMBERIAN VITAMIN C DAPAT MENINGKATKAN KADAR HEMOGLOBIN PADA IBU HAMIL ANEMIA - Risma Agusmayanti; Achmad Farich; Anggraini Anggraini (JKM (Jurnal Kebidanan Malahayati), 2020)
Background: anemia in pregnancy is anemia due to iron deficiency, and is a type of anemia which is relatively easy treatment, even cheap. Efforts to overcome iron nutritional anemia in pregnant women are done through increasing the coverage of iron tablet supplementation, Vitamin C has unstable properties in alkaline solutions, stable in dry conditions and in acidic solutions, and as an iron catalyst so that helps absorption. Preliminary survey conducted by researchers in January 2019 from observations from 3 posyandu in the ANC book found that 65 pregnant women consisted of Posyandu Strawbery 1, namely TM 2 (4 people), TM III (8 people), in Posyandu Strawbery II TM 2 ( 8 people), TM III (23 people). And in the Strawbery III posyandu namely TM 2 (7 people), TM III (15 people). Purpose: of this study is to know the effect of Vit C on hemoglobin levels in pregnant women with anemia in the village of Ringin Sari Banjar Margo, Tuba Tulang Bawang Regency in 2019. Methods: quantitative with pre-experimental action, One group pretest - posttest design. The population in this study were all pregnant women with anemia as many as 65 respondents. A sample of 30 people, the sampling technique used was purposive sampling. Data collection using observation sheets, how to administer Vit C was given 1 day 50 mg to be consumed for 14 days 1x50 mg / day taken after lunch together with FE tablets and the data analysis used was the T-dependent test. Results: of the study are known to be the average value of hemoglobin levels before administration of Vit C 8,980 and standard deviation. The average value of hemoglobin levels after administration of Vit C was 12,190 and a standard deviation of .8397. Conclution: There Is An Effect Of Giving Vit C On Increasing Hb Levels In Pregnant Women (p value 0,0003 <0.05). Suggestions For pregnant women can consume Fe + vit C tablets regularly in order to prevent anemia and to consume foods that contain vitamin C. Suggestion  Pregnant women are expected to routinely take Vit C together with FE tablets at 13 weeks to 40 weeks' gestation, as recommended, so that at the time of delivery the mother does not experience anemia.  Keywords: Anemia, vit C, Hemoglobin ABSTRAK   Latar belakang : anemia pada kehamilan adalah anemia karena kekurangan zat besi, dan merupakan jenis anemia yang pengobatannya relatif mudah, bahkan murah. Upaya penanggulangan anemia gizi besi pada ibu hamil dilakukan melalui peningkatan cakupan suplementasi tablet besi, Vitamin C memiliki sifat yang labil dalam larutan alkali, stabil dalam kondisi kering dan dalam larutan asam, dan sebagai katalisator besi sehingga membantu penyerapan. Survey pendahuluan yang peneliti lakukan pada januari Tahun 2019 dari hasil observasi dari 3 posyandu pada buku ANC diketahui 65 ibu hamil yang terdiri dari posyandu Strawbery 1 yaitu TM 2 (4 orang), TM III (8 orang), di posyandu Strawbery II TM 2 (8 orang), TM III (23 orang). Dan di posyandu Strawbery III yaitu TM 2 (7 orang), TM III (15 orang). Tujuan penelitian :diketahui Pengaruh Vit C terhadap Kadar Hemoglobin Pada Ibu Hamil Anemia didesa Ringin Sari Banjar Margo Kabupaten Tuba Tulang Bawang Tahun 2019.  Metode: kuantitatif dengan tindakan pra eksperimen, rancangan One group pretest – posttest design. Populasi dalam penelitian ini adalah seluruh ibu hamil yang mengalami anemia sebanyak 65 responden. Sampel 30 orang,  Teknik sampling yang digunakan purposive sampling. Pengumpulan data dengan menggunakan lembar observasi,  cara pemberian Vit C diberikan 1 hari 50 mg untuk dikosumsi selama 14 hari 1x50 mg/hari Pemberian Vitamin C Dapat Meningkatkan Kadar Hemoglobin Pada Ibu Hamil Anemiadiminum setelah makan siang bersamaan dengan tablet FE dan analisa data yang digunakan adalah uji Tdependent.  Hasil: diketahui Nilai rata-rata kadar hemoglobin sebelum pemberian Vit C  8.980 dan standar deviasi .8277. Nilai rata-rata kadar hemoglobin sesudah pemberian Vit C  12.190 dan standar deviasi .8397. Kesimpulan:  Ada Pengaruh Pemberian Vit C Terhadap Peningkatan Kadar Hb Pada Ibu Hamil (p value 0,0003 < 0,05). Saran bagi ibu hamil dapat mengkonsumsi tablet Fe + vit C secara rutin guna pencegahan terjadinya anemia serta mengkonsumsi makanan yang mengandung vitamin C. Saran Bagi Ibu Hamil  diharapkan untuk rutin mengkonsumsi Vit C bersamaan tablet FE pada usia kehamilan 13 minggu hingga 40 minggu, sesuai dengan anjuran, agar pada waktu persalinan ibu tidak mengalami anemia  Kata Kunci : Anemia, vit C, kadar